A generalized multiplicative regularization for input estimation. (August 2021) - Aucejo, M.; Smet, O. De
Highlights: A generalized multiplicative regularization parameter is developed in the present paper. The proposed method is applied both numerically and experimentally. Obtained results point out the influence of the additional parameter on the solution accuracy. An original algorithm is implemented to determine the optimal extra tuning parameter. The value of the extra tuning parameter decreases as the measurement noise level increases. Abstract: This paper implements a generalized multiplicative regularization for estimating the mechanical loads acting on a linear structure. The proposed strategy extends the ordinary multiplicative regularization, previously published by the authors, by introducing an extra tuning parameter, which is determined through an original iterative procedure. To assess the practical interest and the overall performances of the proposed approach, numerical and real-world applications are proposed. Obtained results illustrate the influence of the extra tuning parameter according to the measurement noise level and highlight the benefits brought by the generalized multiplicative regularization in terms of solution accuracy.